Clinical Markers of Exercise Intensity as a Surrogate for Blood Lactate Levels Only During Low-Intensity Exercise in Patients With Coronary Artery Disease. Issue 4 (October 2018) - Gurovich, Alvaro N.; Heiser, Brittany; Hayes, Chase; Marshall, Emily; Roath, Stephanie; Kabous, Neil G.
Abstract : Purpose: To determine if clinical markers of exercise intensity, such as heart rate (HR) and rate of perceived exertion (RPE), reflect physiological demands, measured via blood lactate (La) levels, during a graded exercise test (GXT) in cardiac patients. Methods: Thirty-one subjects (19 men and 12 women; age, 58 ± 12 years) were recruited for a GXT. Heart rate, RPE, and La were assessed at rest and after each GXT stage. Pearson correlations were performed between variables (percentage of maximal HR [%HRmax], RPE, La). Bland–Altman analyses were performed to determine agreement between La and %HRmax and RPE. Results: Overall, 113 GXT stages were included in the analysis. It was found that La correlated with RPE (r = 0.72; P < .01) and %HRmax (r = 0.76; P < .01); %HRmax correlated with RPE (r = 0.76; P < .01). However, there was no agreement between La and RPE (72.6% of the sample laid outside 95% CI [−0.25, 0.25 mmol/L]) and between La and %HRmax (85% of the sample laid outside 95% CI [0.54, 1.04 mmol/L]). Conclusions: The significant associations between La, %HRmax, and RPE could be explained by the direct relationship between these variables that occur during the increasing exercise intensity, characteristic of a GTX. However, HR and RPE should not be used as a surrogate to a La-based descriptor of exercise intensity in patients with coronary artery disease exercising at high intensity.